2011
DOI: 10.5507/bp.2011.054
|View full text |Cite
|
Sign up to set email alerts
|

Age, Body Mass Index and Severity of Primary Chronic Venous Disease

Abstract: Aim. The aim of this cross-sectional prospective study was investigate whether there is a correlation between age, BMI and severity of chronic venous disease (CVD), evaluated clinically (CEAP classification) and anatomically (extent of the epifascial venous reflux).Methods. 213 patients, 65 males (30.5%, mean age 45.1±13.9 years) and 148 females (69.5%, mean age 47.5±13.5 years) were divided into three age categories: 18-40 years (40.8%), 41-74 years (56.3%) and ≥75years (2.8%). BMI was classified as normal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 16 publications
7
36
0
9
Order By: Relevance
“…Additionally, obesity is a well-known factor influencing venous blood flow from lower limbs and increases the risk of varicose veins, especially in women [40][41][42][43][44]. In our study, varicose veins were observed more frequently in obese patients.…”
Section: Discussionsupporting
confidence: 56%
“…Additionally, obesity is a well-known factor influencing venous blood flow from lower limbs and increases the risk of varicose veins, especially in women [40][41][42][43][44]. In our study, varicose veins were observed more frequently in obese patients.…”
Section: Discussionsupporting
confidence: 56%
“…6 Unfortunately, individuals with CVD and VLUs experience negative functional and psychological consequences, which lead to low physical activity, 7 increased risk for other comorbid conditions (such as obesity, 8 anxiety and depression, 9 social isolation 10 ), and poor quality of life. 11 The economic burden is enormous.…”
Section: Significancementioning
confidence: 99%
“…гру пи у них зареєстровано достовірно більші значення загального тонусу артерій (на 11,2 %), артерій великого (на 8,2 %), середнього та малого діаметрів (на 13,5 %), часу висхідної частини реовазограми (на 2 %) і повільного кровонаповнення (5,9 %) та достовірно менші дикротичний індекс (на 17 %), тривалість реографічної хвилі (на 3,7 %), час низхідної частини реовазограми (10 %). Виражені зміни реґіонарного кровообігу носять негативний характер, тому що можуть бути ознакою флебопатії -стану, який характеризується наявністю симптомів венозного застою у людей без виявлення виражених клініч-них та інструментальних ознак органічної патології венозної системи [19][20][21][22]. Цей стан, як вважає Савельев [23], є преморбідним щодо варикозної хвороби нижніх кінцівок.…”
Section: результати та їх обговоренняunclassified